Impact of intimate partner violence on clinic attendance, viral suppression and CD4 cell count of women living with HIV in an urban clinic setting - Anderson, Jocelyn C.; Campbell, Jacquelyn C.; Glass, Nancy E.; Decker, Michele R.; Perrin, Nancy; Farley, Jason (AIDS care, 2018)
The substance abuse, violence and HIV/AIDS (SAVA) syndemic represents a complex set of social determinants of health that impacts the lives of women. Specifically, there is growing evidence that intimate partner violence (IPV) places women at risk for both HIV acquisition and poorer HIV-related outcomes. This study assessed prevalence of IPV in an HIV clinic setting, as well as the associations between IPV, symptoms of depression and PTSD on three HIV-related outcomes-CD4 count, viral load, and missed clinic visits. In total, 239 adult women attending an HIV-specialty clinic were included. Fifty-one percent (95% CI: 45%-58%) reported past year psychological, physical, or sexual intimate partner abuse. In unadjusted models, IPV was associated with having a CD4 count <200 (OR: 3.284, 95% CI: 1.251-8.619, p = 0.016) and having a detectable viral load (OR: 1.842, 95% CI: 1.006-3.371, p = 0.048). IPV was not associated with missing >33% of past year all type clinic visits (OR: 1.535, 95% CI: 0.920-2.560, p = 0.101) or HIV specialty clinic visits (OR: 1.251, 95% CI: 0.732-2.140). In multivariable regression, controlling for substance use, mental health symptoms and demographic covariates, IPV remained associated with CD4 count <200 (OR: 3.536, 95% CI: 1.114-11.224, p = 0.032), but not viral suppression. The association between IPV and lower CD4 counts, but not adherence markers such as viral suppression and missed visits, indicates a need to examine potential physiologic impacts of trauma that may alter the immune functioning of women living with HIV. Incorporating trauma-informed approaches into current HIV care settings is one opportunity that begins to address IPV in this patient population.